PENYULUHAN DAN SOSIALISASI APLIKASI BANJARSIHAT UNTUK PENCEGAHAN DAN EDUKASI HIV/AIDS DI DESA KARANG JATI DAN KECAMATAN SUSUKAN - Puspita, Rina; Ulin Nuha ABA, Muhammad; Kuspranoto, Abdul Haris; Rohman Al Ghifari, Ahmad Arif; Maya Rani, Destri; Citra Puspita, Rery Renit (LPPM POLBITRADA, 2025)
The BanjarSihat application outreach and socialization program aims to raise public awareness about HIV/AIDS through a technology-based approach. The program combines three main methods: outreach, training, and mentoring. Outreach is conducted to provide basic information about HIV/AIDS, how it is transmitted, and preventive measures that can be taken. Training is provided to facilitate the use of the BanjarSihat application, which is designed to provide easy access to health information related to HIV/AIDS and other health services. Through mentoring, participants are guided to use the application effectively, ensuring they can access information accurately and use the application's features to monitor their health. The results achieved show a significant impact in increasing awareness about HIV/AIDS in the community. Before using the application, only 40% of participants had a good understanding of HIV/AIDS, but afterwards, this figure increased to 90%. In addition, the use of applications for health education increased from 20% to 80%, and the frequency of HIV/AIDS prevention awareness also increased from 15% to 70%. Community participation in each activity also exceeded the set targets, with counseling and training activities reaching more than 100% of the expected targets. The BanjarSihat application not only provides accurate information but also encourages the community to be more active in HIV/AIDS prevention.